HUBUNGAN PEMBERIAN MP-ASI DINI PADA BAYI DENGAN PENGETAHUAN, SIKAP IBU DAN DUKUNGAN KELUARGA DI KLINIK PRATAMA ROSNI ALIZAR MEDAN : Relationship Between Providing MP-ASI in Babies with Knowledge, Attidute of Mother and Family Support in The Pratama Rosni Alizar Clinic Medan (LPPM - STIKES Pemkab Jombang, 2020)
Introduction: Complementary Food for Early Breast Milk (MP-ASI) is a condition where infants aged 0-6 months are not only given breast milk, but are given additional fluids such as formula milk, oranges, honey, tea and solid foods such as bananas, milk porridge, biscuits, rice porridge, and team rice. Objective: This study was to determine the relationship of knowledge, attitudes, and family support with the provision of early breastfeeding for infants at the Pratama Rosni Alizar Clinic in Medan in 2019. Method: Design this study used an analytical survey with cross sectional approach. The population in this study were all mothers who have babies aged 0-6 months, as many as 30 people. Sampling using total population, that is, the entire population is sampled. Retrieval of data using primary data using Chi-square test at a 95% confidence level. Results and Conclusions: Based on the research showing that there is a relationship between maternal knowledge and the provision of early MP-ASI in infants with the acquisition of p value = 0.027 (<0.05), there is a relationship between maternal attitudes and the provision of early MP-ASI in infants with the acquisition of p value = 0.004 (<0.05), and there is a relationship of family support with early breastfeeding for infants with the acquisition of p value = 0.042 (<0.05).Suggestion:Health workers are expected to provide information and counseling on exclusive breastfeeding for infants up to 6 months of age without providing any additional food. Keywords : Knowledge, Attitude, Family Support, Early MP-ASI